Activity-based costing for competition against generic products: the case of an herbicide product company / Foong Soon-Yau and Ho Ben-Seng - Foong, Soon-Yau; Ho, Ben-Seng (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2009)
Activity-based costing (ABC) enables management to use activity cost information to formulate more effective strategy against competitors. Based on the case of herbicide product company, this paper examines how DCPM, a subsidiary of a multinational company, uses activity cost information to revise its pricing strategy to compete with the generic herbicide products, as the patent protection of its main herbicide product is coming to an end. The management of DCPM faces serious challenges of not only having to sustain its market share but also to achieve the profit target expected by its parent company.